Characteristics of pediatric and adult cases with open globe injury and factors affecting visual outcomes: A retrospective analysis of 294 cases from Turkey - ELBAY, AHMET; Karagoz, Isil Kutluturk; Sari, Esin Sogutlu; KUBALOĞLU, Anil; Elbay, AHMET; ÇALLI, Umit; Pinero, David P.; ÖZERTÜRK, Yusuf; YAZICIOĞLU, Titap (My University, 2018)
BACKGROUND: This study aimed to evaluate 1-year follow-up results of cases that were diagnosed with open globe injury (OGI), to compare trauma-related characteristics between pediatric and adult cases, and to determine risk factors for a poor final visual acuity.